A Brand Recognition of Fish Sauce Origin of Hai Phong through the Case Study of the Retail Market in Hanoi City: Economic - Huu Tung, Phuong (International Journal of Scientific Research and Management (IJSRM), 2021)
Dear Editors!The author is very happy to know the information of the Journal and wishes to submit the article with the topic: "BRAND RECOGNITION OF FISH SAUCE ORIGIN OF HAI PHONG THROUGH THE CASE STUDY OF THE RETAIL MARKET IN HANOI CITY".We hope to receive the attention of the Journal to improve the author's article. The author looks forward to receiving the earliest reply from the editor.Sincerely thank!